PEDAGOGICAL ASPECTS OF USING COLLABORATE LEARNING TECHNOLOGY IN COMPUTER SCIENCES - Kerimbaev, Н.Н.; Sakenova, Ә.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
This article discusses the importance of using collaborative learning technology in computer science lessons and its impact on improving the quality of education. Collaborative learning is a method of solving problems together with each other, in which students work in groups. The article describes the advantages and advantages of this technology, such as increasing student motivation, improving communication skills, developing critical thinking, etc. The scientific definitions of coeducation and the views of foreign scientists are revealed, as well as the basic principles of using this type of training. In society, there is a twin concept known as "co-education" and "co-education". The differences between these two concepts are highlighted and the main forms of joint learning are analyzed. Also, computer science lessons consider various methods and tools with which you can organize cooperation. They Wordwall.net , Flippity.net , LearningApps.org platforms. A comparative analysis of these platforms was carried out and an effective online platform was determined. An example will be considered on a certain online platform and the scope of application will be shown. It is concluded that co-education respects the bilateral strengths and weaknesses of each student, allowing them to grow as part of a team and as individuals.